Rare presentation of odontogenic myxoma - A case report - A C Varsha; Ajay Parihar; Prashanthi Reddy; Ajay L Sutare (Wolters Kluwer Medknow Publications, 2021)
Odontogenic myxoma is a benign locally aggressive odontogenic tumor that arises from the mesenchymal portion of the tooth germ. They occur most frequently in the second or third decade of life and rarely occur before the age of 10 and after the age of 50. These are slow-growing tumors, but they may be locally aggressive, especially in the maxilla. Here we report the case of odontogenic myxoma in a 25-year-old male patient in the mandibular anterior region, which is usually seen in the posterior aspect of the mandible.